2004
DOI: 10.1007/bf03347497
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric, hormonal and biochemical differences in lean and obese women before and after menopause

Abstract: The menopausal status is associated with an increased risk of metabolic and cardiovascular diseases. Since the post-menopausal modifications have not been clearly investigated in obese women, we evaluated the influences of menopausal status on anthropometric, hormonal and biochemical characteristics in selected groups of normal-weight and obese women. We studied 92 female outpatients: 24 normal-weight pre-menopausal (Pre-NW) [body mass index (BMI) 23.6 +/- 0.48, age 44.8 +/- 0.68], 24 normal-weight post-menopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 32 publications
4
19
0
Order By: Relevance
“…We and numerous previous investigators (28,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)42) observed a strong inverse association between SHBG and BMI in premenopausal women. Consistent with this finding, we also observed that free testosterone levels were higher among overweight and obese women compared with normal weight women.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…We and numerous previous investigators (28,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)42) observed a strong inverse association between SHBG and BMI in premenopausal women. Consistent with this finding, we also observed that free testosterone levels were higher among overweight and obese women compared with normal weight women.…”
Section: Discussionsupporting
confidence: 61%
“…Interestingly, we did not observe a similar association with free estradiol, likely due to the lower total estradiol levels in women with high BMI. Although several studies have examined the relationship between current BMI and premenopausal estrogens and androgens, the results are relatively inconsistent (28,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)42). Possible reasons for this may be the small sample sizes (n < 110; refs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Age was strongly associated with obesity in women; prevalence of obesity in women peaked at 53 and above as previously reported by [10]. This association between obesity and age in women can be explained, in part, by parity and post menopausal status [11]. The reduced risk of obesity in younger women may reflect a possible shift in the burden of obesity in women, from the positive association observed in most studies from subSaharan Africa [12,13] to the inverse association reported from developed countries.…”
Section: Discussionsupporting
confidence: 76%
“…This agrees with the previous work of Tufano et al in 44 obese women, half of whom were in the postmenopausal period. FAI was positively related to waist circumference and was significantly higher in menopausal women compared with the premenopausal group (88). In an earlier case-control study of Hauner et al (89) in women undergoing coronary angiography, testosterone was positively associated with the waist:hip ratio, an index of central adiposity, as well as with insulin levels.…”
Section: Obesity-insulin Resistance-metabolic Syndromementioning
confidence: 77%